Diffusing Entrepreneurial Innovation and Tourism: An Empirical Evidence of Permaculture - Umeh Azubuike Lucky; Leilani I. De Guzman; Stephen Ayoade Fadare (Sekolah Tinggi Manajemen IPMI, 2021)
Entrepreneurial innovation and tourism are essential factors in the economic growth of a rural agrarian area. This paper's concept is from Schumpeterian creative destructions' philosophical idea to shift rural communities' mentality from the product-based economy to diverse tourism entrepreneurship. In achieving and sustaining the development of permaculture as a platform for rural agritourism, the social capital theory of collectivism was employed to foster the development that would deliver socio-cultural, environmental, and economic benefits to all stakeholders in the community. This paper employed a descriptive research design to analyze the diffusion of entrepreneurial innovation and tourism systematically; also, to interpret the community's attitude towards the diffusion of permaculture for agritourism. Furthermore, interviews were conducted with the key informant group among the women organization. The paper subjected its participants’ through a non-probability sampling method using cluster sampling in the three barangays of the municipality of Bokod, Province of Benguet. The study results show that the respondents were willing to accept the permaculture for tourism and were willing to commit time to develop and manage the Permaculture project. They were motivated to accept and to participate in the project because they knew the values and benefits that permaculture would bring to the community. Also, while answering contingency valuation questions, the respondent thought about the value and benefits the project would bring. This study will enable communities to develop agritourism through permaculture landscapes in the rural community and, help policymakers in planning sustainable projects to support the community in entrepreneurial innovation.